Analyse systématique du modèle de Bhaduri et Marglin à prix flexibles - Florian Botte; Thomas Dallery (Revue de la Régulation)
The calibration and study of the plausibility of models as much stylized as the post-Kaleckian model are debated. In this article, we present a simulation method allowing to study the stability properties of a model according to its calibration. Instead of calibrating a model with values for unobeservable parameters which produce « realistic » values for equilibrium variables, we propose to look at what happens in a model when one estimates and combines unobservable parameters: does the model produce plausible values for equilibrium variables? We apply this method to the Bhaduri-Marglin model with flexible prices. We show that the model suffers to produce a satisfying number of plausible values for equilibrium variables. We also study the stability conditions (in dimension and in proportion), and we show that some theoretically conceivable configurations do not have numerically plausible counterparts for realistic values of the parameters entering the composition of the model. The precise study of this kind of calibration allows for a reconsideration of the probability to encounter every dynamics which are possible on the analytical ground.